Effect of Li2O addition on sintering and piezoelectric properties of (Ba, Ca)(Ti, Sn)O3 lead-free piezoceramics. Issue 2 (February 2015) - Zhao, Lei; Zhang, Bo-Ping; Zhou, Peng-Fei; Zhu, Li-Feng; Li, Jing-Feng
Abstract This work investigated the enhanced sintering and electrical properties of (Ba0.95Ca0.05)(Ti0.90Sn0.10)O3-xLi2O (BCTSLix, x = 0, 1, 2, 3, 4, 5 and 6 mol%) lead-free piezoelectric ceramics benefiting from the Li2O addition. Highly dense BCTS ceramics with good piezoelectric properties were fabricated at reduced sintering temperatures by adding a small amount of Li2O. It was found that the sintering densification is promoted mainly by reaction liquid phase at the early sintering stage and the formation of oxygen vacancies should be considered as an additional factor. The coexistence of R and T phases was confirmed by the Raman spectrum at a temperature range from−50 °C to 40 °C as x = 2 and at room temperature for all other Li2O added samples, while their specific ratio of R to T phase decreases with increasing Li2O addition. Better properties with d33 = 457 pC/N, kp = 25.18% and Qm = 491 were obtained when adding 4 mol% Li2O, which are attributed dominantly to the appropriate specific ratio of R to T phase because of the similar grain size and density for samples at 3 ≤ x ≤ 6.